Development of the ball-spine algorithm for the shape optimization of ducts containing nanofluid. (16th December 2016) - Hesami, Hanieh; Mayeli, Peyman
ABSTRACT: In this paper a novel shape design method is introduced for the numerical solution of inverse heat convection problems (IHCPs) of nanofluids. The proposed method is a novel extension of the ball-spine algorithm (BSA) inverse method, which is recently adapted for inverse heat transfer problems (IHTPs). Here it is shown how, by a novel physical-sense remedy, the method is applicable to IHCPs as well. In this respect, after validation of the proposed method, two types of IHCPs are introduced and numerically solved. In both types of introduced inverse problems, the objective is shape optimization of a duct containing such steady-state incompressible laminar nanofluid flow that it satisfies a prescribed heat flux distribution along the walls of the geometry. The results show merits and robustness of the BSA application in capturing the target geometry corresponding to a given heat flux distribution in forced heat convection problems with a low computational cost.